History : from the dawn of civilization to the present - Hart-Davis, Adam (New York : Dorling Kindersley Limited, 2015)
Traces the course of human history from prehistoric times to the present day, analyzing the common themes, threads, forces, and factors that have shaped human life--including climate, ecology, disease, and geology--and examining human accomplishments, from the technological innovations that changed the world to key cultural, social, artistic, and intellectual achievements.
Origins -- Rulers & Hierarchies -- Thinkers & Believers -- Warriors, Travelers, & Inventors -- Renaissance & Reformation -- Industry & Revolution -- Population & Power -- National Histories.
Includes index.
Keywords: WORLD HISTORY -- PICTORIAL WORKS